TARGETED RADIOFREQUENCY THERAPY FOR TRAINING INDUCED MUSCLE FATIGUE EFFECTIVE OR NOT (International Journal of Physiotherapy, 2016)
Background: Training induced muscle fatigue (hereinafter also referred as TIMF) is leading to unwanted consequences among sportsmen and actively sporting people such as decreased muscle strength and additional painful discomfort and mobility issues. The knowledge about the mechanisms of influencing the fatigue induced processes in muscle tissue is not comprehensive. The conventional manual techniques, cold patches and conventional physiotherapy have some effect in improving these conditions, however, finding effective methods to influence these consequences appears beneficial in sports medicine. Such method could be Radiofrequency therapy up to 0.5 MHz, known as Targeted Radiofrequency Therapy (hereinafter also referred as TR-Therapy). Aim of this self-controlled study is to evaluate the effect of the TR-Therapy for over-exertion management including the effect on decreased muscle strength, limited range ofmotion and possible painful discomfort.Materials: 7 healthy and actively sporting participants underwent through 2 stages (Active stage – including overexertion of the forearm flexors and subsequent TR-Therapy session; and Control stage - including overexertion of the forearm flexors and subsequent resting period). Data for muscle strength in kg, active Range of Motion (ROM) in (º) and Pain and discomfort perception by 10 point Visual Analog Scale (VAS) were obtained and evaluated.Results: 31% increase in the muscle strength during the active stage was observed and respectively 12% during the control stage, with level of significance p0.05).Conclusions: The results of this study suggest TR-Therapy as effective solution for muscle strength restoration after TIMF.